2009
DOI: 10.1002/anie.200903658
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Six‐Stranded Helical Columns of a Helicene

Abstract: Do the twist: A helicenebisquinone (see formula), both enantiopure and racemic, forms hexagonal columnar phases in which the internal structures of the columns are 132 hollow helices comprising six‐molecule repeat units (see axial and side views). The enantiopure compound forms a true hexagonal structure; the racemate segregates enantiomers into right and left helical columns that are interlocked and longitudinally displaced for optimal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 38 publications
(14 reference statements)
4
47
0
Order By: Relevance
“…The columns of the helicene are believed to be the stiffest among the compounds used in the present study, due to their intertwined 6-strand helical structure shown in Figure 1c. 19 Thus, the observed behavior of the helicene follow the general trend revealed in this study, that axial orientation of the column is promoted by their increasing bending modulus.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The columns of the helicene are believed to be the stiffest among the compounds used in the present study, due to their intertwined 6-strand helical structure shown in Figure 1c. 19 Thus, the observed behavior of the helicene follow the general trend revealed in this study, that axial orientation of the column is promoted by their increasing bending modulus.…”
Section: Resultssupporting
confidence: 71%
“…18 The columns it forms are hollow 13 2 helices with each asymmetric unit comprising six molecules; hence, the columns are rigid six-stranded helices (Figure 1c). 19 The ranking in order of increasing bend elastic constants K 3 should be CBZ dendron, HAT6, HAT6-TNF complex, helicene. The fraction of main (non-H, non-F) atoms in the stiff aromatic portion of the molecule is around 30% for the CBZ dendron and HAT6 and about 40% in the HAT6ÀTNF complex and the helicene.…”
mentioning
confidence: 99%
“…There have been numerous reported examples of intracolumnar helical order in thermotropic 35,36,37 columnar systems -see e.g. review ref.…”
mentioning
confidence: 99%
“…Columnar liquid crystal phases, having 2D positional order, have come a long way since their first discovery in 1977 in discotic molecules . Subsequent years have seen columnar mesogens increasing in complexity and variety of shapes (star, bent core, bowl, helicene, heterocycle, T‐ and X‐shape) and types of non‐bonded interactions (H‐bonding, donor‐acceptor, ionic, coordination) …”
Section: Introductionmentioning
confidence: 99%